Would Surgeons Opt for Polypropylene Mesh if They Hypothetically Had Stress Urinary Incontinence or Pelvic Organ Prolapse?. Issue 4 (19th July 2022) - Devan, William J.; Rodriguez, Dayron; Munarriz, Ricardo; Ng, Linda; Bose, Sanchita
Abstract: Introduction: Mesh is routinely used to treat stress urinary incontinence (SUI) and pelvic organ prolapse (POP). However, its use remains controversial. The FDA (U.S. Food and Drug Administration) ultimately deemed mesh use for SUI and transabdominal POP repair acceptable, while cautioning against transvaginal mesh for POP repair. The objective of this study was to evaluate personal opinions regarding mesh use among clinicians who routinely treat POP and SUI if they themselves were to hypothetically have either condition. Methods: A nonvalidated survey was sent to the Society of Urodynamics, Female Pelvic Medicine, and Urogenital Reconstruction (SUFU) members, and American Urogynecologic Society (AUGS) members. The questionnaire asked participants if they were to hypothetically have SUI/POP which treatment they would elect. Results: A total of 141 participants completed the survey (20% response rate). A significant proportion preferred synthetic mid urethral slings (MUS) for SUI (69%, p <0.001). Surgeon volume was significantly associated with MUS preference for SUI in both univariate and multivariate analyses (OR 3.21 and 3.67, p <0.003). A significant proportion of providers preferred transabdominal repair or native tissue repair for POP (27% and 34% respectively, p <0.001). Private practice was significantly associated with transvaginal mesh preference for POP in univariate analysis but not multivariate analysis (OR 3.45, p <0.04). Conclusions: The use of mesh for SUI and POP has been controversial, leading to the FDA, SUFU and AUGS statements on synthetic mesh use. Our study found that the majority of SUFU and AUGS members who regularly perform these surgeries prefer MUS for SUI. Preferences regarding POP treatments varied.